Rancang Bangun Alat Pemilihan Suara Berbasis Internet of Things Menggunakan Blockchain - Ahmad Saiful Mutaqi Azis; Fara Triadi; Irwansyah Irwansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Manual election processes still face various challenges regarding accuracy, efficiency, and transparency, including the potential for data manipulation and delayed vote recapitulation. This study aims to design and build a prototype Internet of Things (IoT)-based e-voting system integrated with the Hyperledger Fabric permissioned blockchain network, as a solution to improve recording accuracy, process transparency, and recapitulation efficiency. As the problem-solving method, the system architecture comprises an ESP32-S3-based Electronic Voting Machine (EVM), a Node.js Backend API Gateway, and a VotingContract chaincode that enforces election phases, prevents double voting via a voterHash derived from the transient map, and provides real-time result query interfaces. Development followed an Agile Scrum methodology across four sprints: Fabric infrastructure setup, EVM assembly and firmware development, data-schema design with API-ledger integration, and web dashboard development. Testing results demonstrate successful execution of authentication, candidate selection, vote recording with Transaction ID (TxID), tally increments, and rejection of double voting across a 74-transaction simulation without a single failure, without storing voters' personal data on the ledger. The main contribution of this research lies in the direct implementation of the Hyperledger Fabric network on a standalone, resource-efficient ESP32-S3-based EVM hardware terminal, an approach that remains largely unexplored in prior IoT-blockchain e-voting research.